PENERAPAN PEMBELAJARAN TUNTAS UNTUK POKOK BAHASAN GRAMATIKA DAN KOSAKATA DI SMA - Rosyidah Rosyidah; Deddy Kurniawan (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2014)
The study aimed to describe (1) the employment of Mastery Learning method, (2) the student learning outcomes after the implementation of the learning method, and (3) the effectiveness, efficiency and attractiveness of the employment of Mastery Learning method for teaching German grammar and vocabulary in two PASCH-schools in Malang. The study is a qualitative study using a case study design. The research data were collected from German language classes at two PASCH- schools in Malang, SMAN 1 and SMAN 5 Malang. Observations, video recordings, and interviews were used to collect the qualitative data. Data analysis was performed using the interactive model of Miles and Huberman (1984). The findings reveal that (1) the Mastery Learning method was successfully employed at the two PASCH- schools, (2) the students’ mastery of the German grammar and vocabulary ranged from good to very good, and (3) the method was considered effective, efficient, and attractive.